1986
DOI: 10.1067/mva.1986.avs0040129
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of carotid endarterectomy with ocular pneumoplethysmography

Abstract: Objective documentation of the quantitative physiologic changes associated with the repair of carotid lesions of hemodynamic consequence was obtained in 701 procedures by a comparison of pre- and postoperative ocular pneumoplethysmographic tests (OPG-Gee). The results of repair of severe stenoses depended on the status of the carotid artery opposite the repaired vessel. If the vessel opposite the carotid artery repaired was functionally patent, severely stenosed, or totally occluded, the ocular blood flow impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Notably, our findings are reminiscent of the previous studies using ocular pneumoplethysmography, a noninvasive tool to measure ophthalmic pressure to estimate the flow status of ipsilateral intracranial arteries . Abnormalities on ocular pneumoplethysmography were shown more commonly in patients with severe carotid stenosis or occlusions, and those hemodynamic lesions were usually recovered after carotid endarterectomy; both findings are accordant with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, our findings are reminiscent of the previous studies using ocular pneumoplethysmography, a noninvasive tool to measure ophthalmic pressure to estimate the flow status of ipsilateral intracranial arteries . Abnormalities on ocular pneumoplethysmography were shown more commonly in patients with severe carotid stenosis or occlusions, and those hemodynamic lesions were usually recovered after carotid endarterectomy; both findings are accordant with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, attention is focused on detecting patients with cranial hypoperfusion. Evidence suggests that carotid bruit (end‐systolic turbulence in the carotid spectral waveform), 27 ophthalmic artery hypotension on ocular pneumoplethysmography, 28 , 29 an ophthalmic pulse delay on ocular pneumoplethysmography, 30 and decreased middle cerebral artery systolic velocities 14 are such indicators. Ophthalmic artery flow, which appears to be influenced by the ipsilateral grade of internal carotid artery stenosis and symptom status, may prove to be such an indicator as well.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis showed that the ophthalmic artery flow changes after stenting were not statistically different in this group of patients compared to patients with a patent contralateral internal carotid artery. In the study by Gee et al, 28 which studied pre‐ and post‐ocular blood flow in 701 carotid endarterectomy cases using ocular pneumoplethysmography, 27% and 47% improvements on the side of the repaired carotid artery were detected when there was severe stenosis (>70%) and total occlusion of the contralateral carotid artery, respectively. This increase was only 16% when the contralateral side was functionally patent 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPG is also advantageous in that it is an objective process less limited by the operator dependence known in CDUS 22. Further, because choroid blood flow, which makes up the bulk of ocular blood flow, is not autoregulated, it enables detection of hemodynamically significant lesions in a manner more sensitive than autoregulated cerebral blood flow assessable via transcranial Doppler ultrasound 23. However, a limitation is that OPG does not provide information regarding the morphologic characteristics of carotid plaques, which may have prognostic implications regarding likelihood of stroke, although this remains unproven 24,25…”
Section: Discussionmentioning
confidence: 99%